Essays I : Virginibus Puerisque, and other papers - Stevenson, Robert Louis, 1850-1894 (Stevenson, Robert Louis, 1850-1894. Works, 2018)
An analysis of novelistic explorations of modernism in mathematics and its cultural interrelations.